Higher childhood pneumonia admission threshold remains in Lao PDR: an observational study. Issue 10 (18th May 2022) - Lim, Ruth; Chaummanivong, Molina; Taikeophithoun, Chansathit; Gray, Amy; Jenney, Adam W J; Sychareun, Vanphanom; Nguyen, Cattram; Russell, Fiona
Abstract : Objectives: WHO Integrated Management of Childhood Illness (IMCI) guidelines changed pneumonia hospitalisation criteria in 2014, which was implemented in Lao People's Democratic Republic (Lao PDR) in 2015. We determined adherence to: current (2014) IMCI guidelines for children presenting to hospitals with pneumonia, current outpatient management guidelines and identified hospitalisation predictors. Design: Prospective observational study (January 2017 to December 2018). Setting: Outpatient and emergency departments of four hospitals in Vientiane, Lao PDR. Patients: 594 children aged 2–59 months diagnosed with pneumonia. Main outcome measures: Number of children diagnosed, hospitalised, managed, administered preventive measures and followed-up accordant with current guidelines. Results: Non-severe and severe pneumonia were correctly diagnosed in 97% and 43% of children, respectively. Non-severe pneumonia with lower chest wall indrawing (LCI) was diagnosed as severe in 15%. Hospitalisation rates were: 80% for severe pneumonia, 86% and 3% for non-severe pneumonia with and without LCI, respectively. Outpatient oral antibiotic prescribing was high (99%), but only 30% were prescribed both the recommended antibiotic and duration. Appropriate planned follow-up was 89%. Hospitalisation predictors included age 2–5 months (compared with 24–59 months; OR 3.95, 95% CI 1.90 to 8.24), public transport to hospital (compared with private vehicle; OR 2.60, 95% CI 1.09 to 6.24) and households without piped drinking water (OR 4.67, 95% CI 2.75 to 7.95). Conclusions: Hospitalisation practice for childhood pneumonia in Lao PDR remains more closely aligned with the 2005 WHO IMCI guidelines than the currently implemented 2014 iteration. Compliance with current outpatient antibiotic prescribing guidelines was low. Abstract : This study from Lao assesses adherence to the simplified, less parenteral antibiotic focused WHO 2014 pneumonia guidance compared with earlier recommendations.